Muscarinic Receptor Activation Reduces Force and Arrhythmias in Human Atria Independent of IK, ACh. Issue 5 (May 2022) - Petersen, Johannes; Castro, Liesa; Bengaard, Anne K. P.; Pecha, Simon; Ismaili, Djemail; Schulz, Carl; Sahni, Jascha; Steenpass, Anna; Meier, Christian; Reichenspurner, Hermann; Jespersen, Thomas; Eschenhagen, Thomas; et al.
Abstract: In human hearts, muscarinic receptors (M-R) are expressed in ventricular and atrial tissue, but the acetylcholine-activated potassium current (IK, ACh ) is expressed mainly in the atrium. M-R activation decreases force and increases electrical stability in human atrium, but the impact of IK, ACh to both effects remains unclear. We used a new selective blocker of IK, ACh to elaborate the contribution of IK, ACh to M-R activation-mediated effects in human atrium. Force and action potentials were measured in rat atria and in human right atrial trabeculae. Cumulative concentration–effect curves for norepinephrine-induced force and arrhythmias were measured in the presence of carbachol (CCh; 1 µM) or CCh together with the IK, ACh –blocker XAF-1407 (1 µM) or in time-matched controls. To investigate the vulnerability to arrhythmias, we performed some experiments also in the presence of cilostamide (0.3 µM) and rolipram (1 µM), inhibiting PDE3 and PDE4. In rat atria and human right atrial trabeculae, CCh shortened the action potential duration persistently. However, the direct negative inotropy of CCh was only transient in human, but stable in rat atria. In rat and human atria, the negative inotropic effect was insensitive to blockage of IK, ACh by XAF-1407. In the presence of cilostamide and rolipram about 40% of trabeculae developed arrhythmias when exposed to norepinephrine. CCh prevented these concentration-dependent norepinephrine-induced arrhythmias, again insensitive to XAF-1407. Maximum catecholamine-induced force was not depressed by CCh. In human atrium, the direct and the indirect negative inotropic effect of CCh are independent of IK, ACh . The same applies to the CCh-mediated suppression of norepinephrine/PDE-inhibition-induced arrhythmias.